Preparation method of lithium slurry as well as product and application thereof
By etching and passivating the lithium metal material with organic solvents in lithium-ion batteries, a slurry containing lithium particles was prepared, which solved the problems of loss of active lithium and poor safety of lithium supplement agents in lithium-ion batteries, and achieved Lithium secondary battery with high energy density and long cycle life.
Patent Information
- Application Number
- CN202411644543.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-18
AI Technical Summary
During the first charging and discharging process, existing lithium-ion batteries will react sideways with the electrolyte to form a solid electrolyte interface (SEI), resulting in the loss of active lithium and reducing the energy density of the battery. The existing lithium supplements have high cost, poor safety and difficult dispersion, making it difficult to achieve low-cost, high-efficiency and high-safe pre-lithiation.
The lithium-containing metal material is etched and passivated by organic solvents to obtain a slurry of lithium-containing particles, with uniform and controllable particle sizes. This method uses a mixed organic solvent of an etchant and a passivator to etch the grain interface of lithium metal through an etchant, and passivator passivates the grain surface to form stable micron-scale and/or nano-scale lithium-containing particles .
Prelithiation of lithium-ion batteries has been achieved, the energy density and cycle life of lithium secondary batteries has been improved, the cost and operation complexity of batteries have been reduced, and safety and production efficiency have been improved.
Smart Images

Figure CN119481065A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium ion batteries, and more specifically, relates to a method for preparing lithium slurry and its product and application. Background Art
[0002] Lithium-ion batteries have many advantages such as high energy density and long cycle life, and are widely used in digital products, electric transportation and wireless communications. However, during the first charge and discharge process, the negative electrode material of lithium-ion batteries will react with the electrolyte to form a solid electrolyte interface (SEI), resulting in the loss of active lithium, thereby reducing the energy density of the battery. At present, in response to the problem of lithium loss, pre-lithiation technology has been vigorously developed, that is, introducing additional active lithium into lithium-ion batteries to compensate for the irreversible loss of active lithium and improve the energy density of lithium-ion batteries. Among them, the direct contact pre-lithiation using lithium metal powder has the advantages of simple operation, high utilization rate and conducive to industrialization. However, the high cost, poor safety and difficulty in dispersion of commercial lithium powder currently limit the further application of lithium powder. At present, there is a lack of a lithium supplement that is low-cost, high-efficiency, high-safety, simple to operate, low-energy consumption and can be prepared on a large scale.
[0003] Chinese patent CN103943825A discloses a lithium element supplementation method for lithium ion battery electrodes. Although it specifically discloses "preparing a solvent capable of dissolving metallic lithium, dissolving metallic lithium to form a lithium solution", its principle is to use aromatic hydrocarbons and solvents to form a mixed solution to dissolve lithium metal, wherein aromatic hydrocarbons and other substances have a strong electrophilic effect and form lithium-aromatic compounds with lithium. This is a typical chemical pre-lithiation principle, wherein the solvent cannot dissolve lithium metal. When the mixed solution is used, the solvent is easy to remove, but there will be residual aromatic hydrocarbons, causing side reactions to the electrode. Chinese patent CN113300051A discloses a composite method for lithium ion battery pole pieces and diaphragms and a lithium ion battery. Although it specifically discloses "uniformly mixing the lithium powder in the solvent to obtain a lithium powder mixture; in the molten state of the solvent, coating the lithium powder mixture on the surface of the negative electrode", the commercial lithium powder used is generally a particle size of tens of microns and has an inert lithium carbonate layer. It cannot react directly with the electrode when used, and pressure activation is required to promote the reaction of lithium powder with the electrode. In addition, studies have shown that large lithium powder particles cannot be in close contact with the active particles of the electrode (particle size of several microns), and cannot achieve a uniform pre-lithiation effect (for details, see: Jing Ruoying et al., Research progress on pre-lithiation strategies for stable metal lithium powders in lithium-ion batteries, "Chemical Reagents", 2024, 46(07): 66-74.). Summary of the invention
[0004] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for preparing a lithium slurry, a product thereof and an application thereof, wherein an organic solvent is used to etch and passivate a material containing lithium metal (e.g., lithium metal, lithium metal-based composite material, lithium solid solution or lithium solid solution-based composite material) to obtain a slurry containing lithium particles, and the particle size is uniform and controllable. The lithium-containing particle slurry obtained by the present invention can be used for electrode pre-lithiation, the preparation of lithium metal-based electrodes and lithium-based solid-state electrodes, thereby improving the energy density and cycle life of lithium secondary batteries.
[0005] To achieve the above-mentioned object, according to a first aspect of the present invention, a method for preparing a lithium-containing particle slurry is provided, characterized in that the method uses a mixed organic solvent formed by mixing an etchant and a passivator, disperses a material containing lithium metal in the mixed organic solvent, etches the grain boundaries in the material containing lithium metal using the etchant, and passivates the grain surface using the passivator, thereby obtaining a slurry containing stable micron-sized and / or nano-sized lithium-containing particles; wherein the material containing lithium metal has micron-sized and / or nano-sized grains, and the lithium metal is at least one of metallic lithium and a lithium alloy;
[0006] The mixed organic solvent is completely composed of a liquid organic solvent, wherein the etchant is selected from at least one of diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), ethanol (EtOH), and dimethyl sulfoxide (DMSO);
[0007] The passivating agent is selected from at least one of ethylene carbonate (EC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), 1,3-dioxane (DOX), and trioxane (TO);
[0008] The volume percentage of the passivating agent in the mixed organic solvent is 5%-50%.
[0009] As a further preferred embodiment of the present invention, the material containing lithium metal is at least one of lithium metal, lithium alloy, lithium metal-based composite material, lithium solid solution, and lithium solid solution-based composite material;
[0010] The metal lithium-based composite material is a composite material of lithium metal and carbon material, or a composite material of lithium metal and solid electrolyte;
[0011] The elements contained in the lithium solid solution, in addition to the Li element, also include at least one of the following elements: silver element, magnesium element, gold element, zinc element, aluminum element, and platinum element;
[0012] The lithium solid solution-based composite material is a composite material of a lithium solid solution and a carbon material, or a composite material of a lithium solid solution and a solid electrolyte;
[0013] The lithium-containing particles are in the form of at least one of spheres and flakes;
[0014] The surface of the lithium-containing particle has an interface structure generated by passivation, and the interface structure is at least one of an organic substance or an organic-inorganic composite.
[0015] As a further preferred embodiment of the present invention, after dispersing the lithium metal-containing material in the mixed organic solvent, the reaction system is further stirred to accelerate the reaction.
[0016] As a further preferred embodiment of the present invention, after the reaction, the slurry of the lithium-containing particles is further added with a functional additive; the functional additive is selected from: at least one of ethylenediaminetetraacetic acid, silane coupling agent, thiourea, polyacrylic acid, polyvinylidene fluoride, polyethylene glycol, glycerol, polyethylene oxide, silver nitrate, silver fluoride, and tin fluoride; or selected from: alkyl lithium, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium difluorobis(oxalatophosphate), nitric acid. At least one of lithium, lithium fluoride, lithium nitride, lithium oxide, lithium carbonate, lithium hydroxide, lithium hydride, aryl lithium, lithium amide, lithium phosphorus sulfur, lithium lanthanum zirconium oxide, lithium iodide, lithium naphthalene, lithium anthracene, and lithium biphenyl; or at least one of carbon black, carbon nanotubes, vapor-grown carbon fiber reinforcement, graphene, acetylene black, and Ketjen black; or at least one of nitrogen diisobutyronitrile, azodiisopropylbenzene, dibenzoyl peroxide, dilauroyl peroxide, 1,3,2-dioxathiophene-2,2-dioxide, tin trifluoromethanesulfonate, and magnesium trifluoromethanesulfonate;
[0017] The mass percentage of the functional additive in the slurry obtained after adding is 0-50%.
[0018] According to the second aspect of the present invention, the present invention provides a lithium-ion battery pre-lithiation electrode, characterized in that the slurry of lithium-containing particles obtained by the above preparation method is loaded on the electrode of the lithium secondary battery, so that pre-lithiation can be completed after injecting the electrolyte.
[0019] As a further preferred embodiment of the present invention, the loading is achieved by dripping, coating, spraying, spinning or 3D printing.
[0020] According to the third aspect of the present invention, the present invention provides a lithium metal-based electrode, characterized in that the slurry of lithium-containing particles obtained by the above preparation method is loaded on a current collector to form a lithium metal-based electrode on the current collector; or the slurry of lithium-containing particles obtained by the above preparation method is assembled with a supporting material into a self-supporting film to obtain a lithium metal-based electrode.
[0021] As a further preferred embodiment of the present invention, the loading is achieved by dripping, coating, spraying, spinning or 3D printing; the supporting material is selected from carbon nanotubes and carbon fibers;
[0022] The thickness of the lithium metal-based electrode is 0.1-100 μm 。
[0023] According to the fourth aspect of the present invention, the present invention provides a lithium-based solid electrode, characterized in that the lithium-containing particle slurry obtained by the above preparation method is compounded with a lithium battery solid electrolyte to obtain an integrated lithium-based solid electrode.
[0024] According to a fifth aspect of the present invention, the present invention provides the use of the above-mentioned lithium-ion battery pre-lithiation electrode, the above-mentioned lithium metal-based electrode, or the above-mentioned lithium-based solid-state electrode in a lithium secondary battery.
[0025] Compared with the prior art, the above technical solutions conceived by the present invention can achieve the following
[0026] Beneficial effects:
[0027] (1) The present invention can control the preparation of lithium-containing particle slurry, and utilize the selective etching reaction of the solvent on the lithium metal grain boundary. The etchant preferentially etches the lithium grain boundary with high activity, thereby promoting the effective separation of lithium particles of the lithium foil. Furthermore, the passivator is used to protect the etched interface and inhibit the further reaction of the etchant, thereby ensuring the activity of the lithium particles obtained by the etching reaction. And the prepared lithium particles maintain the original stable structure, so they have good stability and reactivity. By optimizing the components and ratios of the etchant and the passivator, the rate of the etching reaction can be effectively regulated. The lithium metal-containing material (such as lithium foil, lithium ingot, lithium alloy, etc.) used in the lithium-containing particle slurry preparation method of the present invention has micron-level and / or nano-level grains, and the material is easy to obtain. Taking lithium foil as an example, the grain size and shape of the lithium foil can be regulated by the structural regulation methods such as annealing, rolling, melting, alloying, etc. known in the prior art, so that lithium particles with different grain sizes can be accurately and controllably prepared based on the method of the present invention. It is preferred that lithium-containing particles of different forms can be obtained by selecting suitable functional additives and regulating reaction conditions.
[0028] (2) The lithium-containing particle slurry obtained by the one-step method of the present invention has the advantage of stable properties. The passivating agent can stabilize the lithium particles formed in situ. Since the initial lithium-containing particle slurry does not contain lithium salt, the stable existence of lithium particles can be guaranteed (lithium salt has poor air stability and will decompose and produce acid when in contact with air, resulting in lithium inactivation). Since the lithium particles are evenly dispersed in the solvent, the risk of explosion caused by direct contact of lithium powder with air is avoided.
[0029] (3) The lithium powder particles prepared in the present application are small, with diameters of micrometers and nanometers (as exemplified in Example 4 below, the diameter of the product lithium powder particles is about 1 μm), and lithium powder particles smaller than common lithium powder (generally greater than 10 μm) can be obtained. Small-particle lithium powder can be evenly distributed on the surface of the electrode, and can enter the interior of the electrode along the electrode pores, thereby improving the uniformity of pre-lithiation of the electrode scale. In addition, due to the direct synthesis of the lithium-containing particle slurry, in which the lithium powder is not in contact with the air, there is only an interface formed by the passivator, and the interface layer will be dissolved in the organic solvent, so the lithium powder interface is thin and the surface activity is high, and there is no thick lithium carbonate passivation layer of commercial lithium powder. Considering the instability existing in the preparation and transportation process of commercial lithium powder, it is necessary to passivate the surface to improve the air stability, but this also causes difficulties in the use of lithium powder. The lithium powder needs to be crushed before use, and the passivation layer will be retained as a residue. When used for pre-lithiation, it will cause excessive impurities on the electrode surface, causing a decrease in the electrochemical activity of the electrode.
[0030] (4) The method for preparing lithium-containing particle slurry of the present invention is low-cost and simple to operate. Only cheap and readily available solvents are used to react with lithium metal to obtain lithium particles. During the reaction, only simple stirring treatment (the rotation speed can be, for example, 100-2000 rpm) can be applied. No complex and dangerous operation methods such as ultrasonic crushing, shaking, and melting are required. The solvent can be recycled and reused, which can greatly reduce the cost of pre-lithiation. In addition, the organic solvent is easy to volatilize without residue, reducing the subsequent cleaning steps. It has the advantages of simple operation, low production cost, and easy industrialization.
[0031] (5) The lithium-containing particle slurry of the present invention has the advantages of being simple and efficient when used. The lithium-containing slurry in which the lithium particles are formed in situ and evenly dispersed is directly used as a lithium supplement, without the need for complex operation steps such as dispersing and activating lithium powder. Since the lithium powder is distributed in the solvent, the risk of explosion caused by contact with air is avoided, and safety is also improved.
[0032] (6) The lithium-containing particle slurry prepared by the present invention is compatible with both liquid battery and solid-state battery processes, is simple to operate, and is suitable for industrial applications. By polymerizing the lithium-containing particle slurry in situ, the lithium powder can be effectively locked to prevent it from moving freely and leaking in the battery cell, thereby improving safety. By compositely assembling the solid electrolyte and the lithium-containing particle slurry into an integrated electrode, the interface impedance can be reduced, the carrier transfer rate can be increased, and a three-dimensional structure can be constructed to increase the electrochemically active specific surface area, thereby improving the electrochemical activity and reducing the risk of dendrites.
[0033] (7) The lithium solid solution / composite lithium in the lithium-containing particle slurry prepared by the present invention can not only replenish lithium, but also serve as an electrode kinetics promoter to promote carrier transport, improve electrochemical activity and reduce the risk of lithium precipitation. Therefore, the lithium-containing particle slurry can improve the kinetics of silicon-based negative electrodes and solid-state batteries.
[0034] (8) The lithium-containing particle slurry prepared by the present invention can be used for pre-lithiation of positive and negative electrodes at the same time. The high reactivity of lithium powder to the positive electrode may cause damage to the positive electrode, which can be solved by regulating the activity of the lithium-containing particle slurry, such as preparing high-potential lithium alloy, passivation layer, and buffer interface structure. At the same time, pre-lithiation of positive and negative electrodes, including lithium replenishment of silicon-based negative electrodes, over-lithiation of lithium-containing positive electrodes, and lithium replenishment of lithium-free positive electrodes (sulfur positive electrodes), can further improve the energy density of lithium-ion batteries.
[0035] (9) In addition, based on the present invention, by adjusting the functional additives in the obtained lithium-containing particle slurry, the properties of the slurry can be flexibly adjusted and improved. By adding refined lithium particles and pore-forming additives, nanoscale and porous lithium particles can be obtained; by adding surface stabilizers, the air stability of the lithium-containing particle slurry can be improved; by adding lithium conductive / electric additives, the electrochemical properties of pre-lithiation electrodes, lithium metal-based electrodes and lithium-based solid-state electrodes can be enhanced. For example:
[0036] a. The optional functional additives can further modify the lithium particles to improve the interface stability, including but not limited to: at least one of ethylenediaminetetraacetic acid, silane coupling agent, thiourea, polyacrylic acid, polyvinylidene fluoride, polyethylene glycol, glycerol, polyethylene oxide, silver nitrate, silver fluoride, and tin fluoride;
[0037] b. The optional functional additives can further improve the ionic conductivity of the lithium-containing particle slurry, including but not limited to: at least one of alkyl lithium, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium difluorobis(oxalatophosphate), lithium nitrate, lithium fluoride, lithium nitride, lithium oxide, lithium carbonate, lithium hydroxide, lithium hydride, aryl lithium, lithium amide, lithium phosphorus sulfur, lithium lanthanum zirconium oxide, lithium iodide, lithium naphthalene, lithium anthracene, and lithium biphenyl;
[0038] c. The optional functional additives can further improve the electronic conductivity of the lithium-containing particle slurry, including but not limited to: at least one of carbon black, carbon nanotubes, vapor-grown carbon fiber reinforcement, graphene, acetylene black, and Ketjen black;
[0039] d. Optional functional additives can further promote the in-situ polymerization reaction of the lithium-containing particle slurry, including but not limited to: at least one of diisobutyronitrile, azodiisopropylbenzene, dibenzoyl peroxide, dilauroyl peroxide, 1,3,2-dioxazolidinone-2,2-dioxide, tin trifluoromethanesulfonate, and magnesium trifluoromethanesulfonate.
[0040] Due to the high reactivity of lithium metal, in order to obtain stable lithium powder, a common method is to use an inert solvent to react with lithium metal to obtain lithium powder. Chinese patent CN108832116A discloses a flaky metal lithium powder and a preparation method thereof, which ultrasonically crushes metal lithium in a low-viscosity inert organic solvent by vacuum ultrasonic crushing to prepare micron-level flaky metal lithium powder. It can be seen that the lithium powder preparation process generally uses mechanical force (complex and dangerous operation methods such as ultrasonic crushing, vibration, melting, etc.) to crush lithium metal, and then uses an inert organic solvent to disperse the crushed lithium powder, so the organic solvent needs to remain inert and not react with the lithium powder. However, this method has the risk of causing an explosion when in contact with air. The present invention promotes the etching of lithium metal grain boundaries through chemical reactions by selectively introducing a solvent (etchant) that reacts with lithium metal, thereby achieving the effect of chemically crushing lithium metal. The method is simple, safe, and environmentally friendly; the introduction of a solvent (passivator) that passivates the surface of lithium metal can inhibit the continuous reaction of the etchant to the lithium metal interface. By optimizing the ratio of the etchant and the passivator and coordinating the effects of the two, a stable lithium-containing particle slurry can be obtained, and this method is a one-step reaction and does not require complicated operating steps. In addition, the slurry containing stable lithium-containing particles can be directly used for the pre-lithiation operation of the electrode, without the need for special solvent dispersion and pressure activation operations when commercial lithium powder is used. Taking the flaky lithium-containing particles synthesized by the method of the present invention as an example, the lithium-containing particles are of micro-nano scale and can be in close contact with the electrode without external pressure, thereby promoting the uniformity of the pre-lithiation reaction. As described later Fig.15 As shown, the lithium powder interface layer structure prepared based on the method of the present invention is an organic-inorganic composite interface with a thickness of 10 nm. Compared with the inorganic structure, the interface structure is relatively loose, which is conducive to lithium ion conduction and thus has a good pre-lithiation efficiency.
[0041] In the preparation method of the lithium-containing particle slurry of the present invention, it is necessary to first mix the etchant and the passivator to prepare a mixed organic solvent, and then add the material containing lithium metal to the mixed organic solvent. The mixed organic solvent is completely composed of an organic solvent and does not contain any other solute (especially does not contain a lithium metal salt). The ratio of the etchant and the passivator in the mixed organic solvent is very critical. Only with a suitable ratio can a good etching-passivation effect be achieved and stable lithium-containing particles can be obtained. In the method of the present invention, the etchant is at least one of DEC, DMC, EMC, NMP, DMF, EtOH, and DMSO, and the passivator is at least one of EC, FEC, VC, DME, DOL, DOX, and TO. Although these etchants and passivators are both organic solvents, their functions are different; the etchant is used to etch the grain boundaries in the raw material (i.e., the material containing lithium metal), and the passivator is used to passivate the surface of the grains. It is by controlling the volume ratio of the passivator to the etchant to (5%-50%): (50%-95%) that stable lithium-containing particles are obtained. In addition, the obtained lithium-containing particle slurry has good calendar aging life and air stability. This is also due to the control of the ratio of the etchant to the passivator by the present invention, so that stable lithium-containing particles with a passivation interface layer are obtained, and the passivation interface layer can effectively isolate the etchant and the air.
[0042] In summary, the present invention can achieve the granulation of lithium metal through a simple etching-passivation mechanism, prepare lithium-containing particle slurry and use it for the preparation of pre-lithiation electrodes, lithium metal-based electrodes and lithium-based solid-state electrodes, thereby improving the energy density of lithium secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Optical microscope photos of lithium foil before and after adding DEC; Figure 1 (a) corresponds to the original lithium foil, Figure 1 (b) in the figure corresponds to the reaction after adding DEC.
[0044] Figure 2 The voltage-time curve of lithium-copper battery with DEC and EC solvents added.
[0045] Figure 3 This is a photo of lithium metal reacting with EC / DEC mixed solvent.
[0046] Figure 4 XRD diagram of lithium-containing particle slurry (Li slurry) and lithium foil (Li).
[0047] Figure 5 This is the SEM image of lithium particles in the lithium-containing particle slurry.
[0048] Figure 6This is an optical microscope photo of the silicon-carbon negative electrode sheet loaded with lithium particles before and after the addition of electrolyte; Figure 6 (a) corresponds to before injection. Figure 6 (b) in the figure corresponds to the state after injection.
[0049] Figure 7 This is a comparison of the first charge and discharge curves of the pre-lithiation silicon-carbon anode (Si / C+Li) and the original silicon-carbon anode (Si / C).
[0050] Figure 8 Comparison of the time-specific capacity curves of a half-cell assembled with a pre-lithiated silicon anode and a half-cell assembled with a pristine silicon-carbon anode.
[0051] Fig. 9 Comparison of the first charge and discharge curves of a full battery assembled with pre-lithiated silicon anode and lithium cobalt oxide cathode and a full battery assembled with original silicon-carbon anode and lithium cobalt oxide cathode.
[0052] Fig.10 Comparison of the time-specific capacity curves of a full battery assembled with a pre-lithiated silicon negative electrode and a lithium cobalt oxide positive electrode and a full battery assembled with an original silicon-carbon negative electrode and a lithium cobalt oxide positive electrode.
[0053] Fig.11 Comparison of the capacity retention rates of a full battery assembled with pre-lithiated graphite anode and nickel cobalt manganese oxide cathode and a full battery assembled with pristine graphite anode and nickel cobalt manganese oxide cathode.
[0054] Fig.12 Comparison of the capacity retention rates of full batteries assembled with alloy thin lithium negative electrode and lithium cobalt oxide positive electrode and full batteries assembled with commercial thin lithium and lithium cobalt oxide positive electrode.
[0055] Fig.13 Comparison of the capacity retention rates of all-solid-state batteries assembled with three-dimensional composite alloy negative electrode and nickel cobalt manganese oxide positive electrode and all-solid-state batteries assembled with commercial thin lithium and nickel cobalt manganese oxide positive electrode.
[0056] Fig.14 This is a comparison chart of the capacity retention rate of polymer solid-state full batteries before and after the introduction of high-entropy lithium-containing particle slurry.
[0057] Fig.15 It is the XPS graph of lithium-containing particle slurry before and after argon ion etching; Among them, Fig.15 (a) and (b) correspond to before argon ion etching. Fig.15 (c) and (d) correspond to argon ion etching for 50 seconds (etching depth is 10 nm).
[0058] Fig.16 This is a photo of lithium-containing particle slurry placed in the air; Fig.16a in the table is the initial state after preparation (recorded as day 0), Fig.16 b in the figure is the state after 1 day of storage (recorded as Day 1). Fig.16 The c in the figure is the state after being placed for 7 days (recorded as the 7th day).
[0059] Fig.17 This is the SEM image of lithium particles in the lithium-containing particle slurry.
[0060] Fig.18 This is the SEM image of lithium particles in the lithium-containing particle slurry.
[0061] Fig.19 Schematic diagram of the preparation of lithium-containing particle slurry of the present invention. DETAILED DESCRIPTION
[0062] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0063] The lithium foils used in the following examples are all commercial lithium foils (also called commercial thin foils) purchased from Zhongneng Lithium Industry, with a thickness of 50 μm.
[0064] Embodiment 1
[0065] Under an inert atmosphere, DEC was drop-coated on lithium foil and allowed to stand for 10 h.
[0066] Figure 1 This is an optical microscope photo of the lithium foil prepared in Example 1 after adding DEC to react. As can be seen from the figure, the surface of the original lithium foil is uniform and shiny before the reaction, and cracks appear at the grain boundaries of the lithium foil after the reaction. This result shows that DEC reacts along the grain boundaries of lithium metal to etch the grain boundaries.
[0067] Embodiment 2
[0068] Two samples were prepared in this embodiment:
[0069] Sample A: Under an inert atmosphere, 50 μL of DEC was added as an electrolyte to a lithium-copper battery (lithium as the negative electrode and copper as the positive electrode) and the battery was left to stand to monitor changes in its open circuit potential.
[0070] Sample B: Under an inert atmosphere, 50 μL of DEC was added to a lithium copper battery (lithium as the negative electrode and copper as the positive electrode) and left to stand, and the change in its open circuit potential was monitored. After DEC reacted with lithium metal for one hour, the battery was disassembled and 50 μL of EC solvent was injected, the battery was reassembled, and the battery was left to stand and the potential change was monitored.
[0071] Figure 2 This is the voltage-time curve of the lithium copper battery prepared in Example 2. It can be seen from the "DEC-20h" curve (corresponding to sample A) in the figure that after adding DEC to the lithium copper battery, the potential continues to decrease, indicating that the DEC solvent continues to react with lithium metal. Therefore, DEC is an etchant and will continue to react with metallic lithium. The reason is that the product generated by the reaction of DEC and lithium metal is not dense enough to prevent further reaction.
[0072] From the "DEC-1h+EC-19h" curve (corresponding to sample B) in the figure, it can be seen that after adding EC, the potential of the lithium copper battery is increased to about 2V and remains stable, and there is no continuous decrease in potential. Therefore, it can be explained that EC can also react with lithium metal and form a stable interface layer on the surface of lithium metal, inhibiting the continuous reaction of the solvent (EC or DEC). Therefore, EC is a passivating agent, which will react with lithium metal and passivate the interface, inhibiting the continuous reaction of the etchant and lithium metal.
[0073] The present invention experiments with a variety of organic solvents in this way, and proves that dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), ethanol (EtOH), dimethyl sulfoxide (DMSO) are similar to DEC and are etchants; fluoroethylene carbonate (FEC), vinylene carbonate (VC), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), 1,3-dioxane (DOX), trioxane (TO) are similar to EC and are passivators.
[0074] Embodiment 3
[0075] Under an inert atmosphere, solvents with different EC / DEC ratios were prepared, and lithium metal was added for reaction (the raw material lithium metal used had micron-sized crystals), and the reaction was accelerated by stirring for 5 hours.
[0076] Figure 3This is a reaction photograph of lithium metal and EC / DEC mixed solvent prepared in Example 3. As can be seen from the figure, when lithium metal is added to EC (i.e., EC:DEC=10:0), it still maintains its original morphology and gloss, indicating that EC will passivate the lithium metal interface and will not react continuously. When the EC / DEC volume ratio is 9 / 1, the lithium metal partially reacts and large pieces of lithium metal foil still exist. When the EC / DEC volume ratio is in the range of (5 / 5) to (1 / 19), a uniform lithium slurry appears, indicating that this ratio can balance the synergistic effect of EC and DEC, exert the etching agent effect of DEC and the passivating agent effect of EC, thereby breaking up and stabilizing the lithium particles and obtaining a stable lithium-containing particle slurry. When the EC / DEC volume ratio is 1 / 49, the slurry turns black and the particulate content decreases, indicating that EC can no longer balance the effects of the etchant and the passivating agent, resulting in a continuous reaction of the lithium particles. When the EC / DEC volume ratio is in the range of (1 / 99) to 0, the particles completely disappear and the color turns brown, indicating that DEC continuously reacts with lithium metal and lithium is completely deactivated.
[0077] Therefore, it can be defined that the solvent that continuously reacts with lithium metal and cannot form a stable interface is an etchant, and the solvent that reacts with lithium metal to form a stable interface and inhibits continuous reaction is a passivator. When the mixed solvent of the etchant and the passivator reaches a suitable ratio, the lithium metal can be etched and the interface can be passivated to obtain a stable lithium-containing particle slurry.
[0078] Embodiment 4
[0079] Preparation of the original electrode sheet: Take 0.8g of silicon-carbon powder, 0.1g of conductive agent (carbon black) and 0.1g of binder (polyacrylic acid), mix the weighed materials evenly, slurry them, coat them on copper foil, bake them at 80°C under vacuum conditions for 24h, and punch them into silicon-carbon electrodes (Si / C) with a diameter of 10mm.
[0080] Loading lithium slurry and constructing half-cell: Under an inert atmosphere, add 0.01g lithium foil (with micron-sized grains) to 1mL EC / DEC organic solvent (volume ratio 1:1) and stir (speed 200rpm). After 5h, lithium-containing particle slurry (Li slurry) containing lithium particles is obtained. 20μL of lithium-containing particle slurry is dripped on the pole piece, and after drying, a silicon-carbon negative electrode pole piece (Si / C+Li) of composite lithium powder is obtained. The silicon-carbon pole piece of composite / uncomposite lithium powder is assembled with lithium metal half-cells, and the electrolyte (1.0M LiPF6 in EC:EMC:DMC=1:1:1, volume ratio) is added to test the electrochemical performance of the half-cell (wherein, the silicon-carbon pole piece without composite lithium powder, that is, the original silicon-carbon negative electrode Si / C, is assembled with lithium metal half-cells, which serves as a control).
[0081] Figure 4This is a comparison of the XRD patterns of the lithium slurry (Li slurry) and lithium foil (Li) synthesized in Example 4. As can be seen from the figure, the XRD of commercial lithium foil (Li) has three main peaks, at 36°, 52° and 65°, corresponding to the (110), (200) and (211) crystal planes of lithium. The XRD pattern of the lithium-containing particle slurry formed by the reaction implemented by the present application has only one obvious characteristic peak, at 36° corresponding to the (110) of lithium.
[0082] Figure 5 The morphology of lithium particles in the lithium-containing particle slurry synthesized in Example 4. As can be seen from the figure, the morphology of the lithium particles is a nano-flake of 1 μm level.
[0083] Figure 6 This is an optical microscope photo of the electrode before and after the addition of the electrolyte to the silicon-carbon electrode loaded with lithium-containing particle slurry prepared in Example 4. As can be seen from the figure, before injection, the flaky lithium particles are evenly distributed on the electrode surface, tightly attached to the surface of the silicon-carbon particles, and the lithium particle size is about 1μm. After the electrolyte is added and allowed to stand, the lithium powder particles basically react and disappear. This result shows that the generated lithium powder is highly active, and the flaky structure of the lithium powder can promote its close contact with the electrode, so it has the advantage of no residue after the reaction.
[0084] Figure 7 This is the first charge and discharge curve of the silicon-carbon half-cell prepared in Example 4. At room temperature, the battery is charged and discharged at a constant current of 100mA / g, and the voltage range is 0.01V-1V. As can be seen from the figure, the potential of the silicon-carbon negative electrode of the composite lithium-containing particle slurry is reduced to 0.6V after standing for 10h, and the discharge specific capacity is 1500mAh / g, which is 200mAh / g less than the discharge specific capacity of the original silicon-carbon negative electrode, indicating that the silicon-carbon negative electrode of the composite lithium powder undergoes a pre-lithiation reaction in situ after the addition of the electrolyte, successfully compensating for the loss of active lithium. Moreover, as shown in the figure, the charge specific capacity of the pre-lithiated silicon-carbon negative electrode is consistent with that of the non-pre-lithiated one, indicating that this method will not cause side reactions to the silicon-carbon negative electrode.
[0085] Embodiment 5
[0086] Preparation of the original electrode sheet: Take 0.8g of silicon powder, 0.1g of conductive agent (carbon black) and 0.1g of binder (polyacrylic acid), mix the weighed materials evenly, slurry them, coat them on copper foil, bake them at 80℃ and vacuum conditions for 24h, and punch them into silicon electrodes (Si) with a diameter of 10mm.
[0087] Lithium-loaded slurry: Under an inert atmosphere, 0.02 g of lithium-phosphorus alloy foil (with micron-sized grains and a phosphorus mass percentage of 20%) was added to 1 mL of FEC / DEC organic solvent (volume ratio 1:1) and stirred (speed 800 rpm). After 5 hours, a lithium-containing particle slurry containing lithium-phosphorus alloy particles was obtained. 50 μL of the lithium-containing particle slurry was dripped onto the silicon pole piece, and after drying, a composite lithium-phosphorus alloy silicon negative pole piece (Si+Li) was obtained.
[0088] Preparation of positive electrode and construction of battery: Take 0.9g lithium cobalt oxide powder, 0.05g conductive agent (carbon black) and 0.05g binder (polyvinylidene fluoride), mix the weighed materials evenly, slurry, coat on aluminum foil, bake at 80℃ and vacuum conditions for 24h, and punch into lithium cobalt oxide electrodes (LCO) with a diameter of 10mm. Assemble half-cells with silicon negative electrodes containing / not containing lithium and lithium, respectively, assemble ampere-hour-level laminated soft-pack full batteries with silicon negative electrodes containing / not containing lithium and lithium cobalt oxide positive electrodes, add electrolyte (1.0MLiPF6in EC:EMC:DMC=1:1:1, volume ratio), and test the electrochemical performance of silicon half-cells and full batteries (wherein, the use of silicon negative electrodes without lithium, that is, the original silicon electrode Si, to construct half-cells and full batteries serves as a control).
[0089] Figure 8 The time-charging capacity curve of the silicon half-cell prepared in Example 5 shows that the cycle stability of the pre-lithiation silicon battery is improved and the charging capacity is also increased by 100 mAh g -1 , indicating that lithium-phosphorus alloy can improve the reaction kinetics of the electrode, thereby improving the reversible capacity of the electrode.
[0090] Fig. 9 This is the first charge and discharge curve of the soft-pack full battery prepared in Example 5. Under room temperature, the battery was charged and discharged at a constant current of 200 mA, and the voltage range was 4.3-2.5 V. As can be seen from the figure, compared with the soft-pack full battery without the introduction of lithium-containing particle slurry, the discharge specific capacity of the silicon negative electrode assembled full battery with the introduction of lithium-containing particle slurry increased by 550 mAh / g, indicating that the introduction of lithium-containing particle slurry successfully compensated for lithium loss and achieved pre-lithiation of the electrode. Fig.10 The time-capacity curve of the full battery shows that the capacity retention rate of the pre-lithiated full battery after 400 cycles at 4C high rate is 100%, while the retention rate of the non-pre-lithiated full battery after 90 cycles is 80%. This result shows that pre-lithiation can improve the cycle life and rate performance of the full battery.
[0091] Embodiment 6
[0092] Lithium-loaded slurry: In an inert atmosphere, silver and lithium metal were mixed and rolled to obtain a lithium-silver alloy (with micron-sized grains and a silver mass percentage of 10%), and 0.04 g of lithium-silver alloy foil was added to 1 mL of VC / DOL / DEC organic solvent (volume ratio 1:1:8) and stirred for 1 h to obtain a lithium-containing particle slurry containing lithium-silver alloy particles. 1 g of graphite negative electrode powder (Gr) was added to the lithium-containing particle slurry and stirred for 2 h, and after drying, a graphite negative electrode powder (Gr+Li) of a composite lithium-silver alloy was obtained.
[0093] Preparation of composite graphite pole piece: Take 0.9g composite graphite powder (Gr+Li) with 0.05g conductive agent (acetylene black) and 0.05g binder (polyacrylic acid), mix the weighed materials evenly, slurry them, coat them on copper foil, bake them at 80℃ and vacuum conditions for 24h, and punch them into electrodes with a diameter of 10mm to obtain composite graphite electrode (Gr+Li).
[0094] Preparation of graphite pole piece (as control sample): Take 0.9g graphite powder (Gr) with 0.05g conductive agent (acetylene black) and 0.05g binder (polyacrylic acid), mix the weighed materials evenly, slurry them, coat them on copper foil, bake them at 80℃ and vacuum conditions for 24h, punch them into electrodes with a diameter of 10mm, and obtain graphite electrode (Gr) as control sample.
[0095] Preparation of positive electrode sheet: Take 0.9g of lithium nickel cobalt manganese oxide powder, 0.05g of conductive agent (carbon black) and 0.05g of binder (polyvinylidene fluoride), mix the weighed materials evenly, slurry them, coat them on aluminum foil, bake them at 80°C under vacuum conditions for 24h, and punch them into electrodes (NCM) with a diameter of 10mm.
[0096] Building batteries: Assemble the composite graphite negative electrode sheet (Gr+Li) and the nickel cobalt manganese oxide positive electrode into a full battery, and assemble the graphite negative electrode sheet (Gr) and the nickel cobalt manganese oxide positive electrode into a full battery, add electrolyte (1.0M LiPF6 in EC:EMC:DMC=1:1:1, volume ratio), and test the electrochemical performance of the full battery (wherein, the use of the original graphite negative electrode sheet Gr to build the full battery serves as a control).
[0097] Fig.11 This is the capacity retention rate diagram of the full battery prepared in Example 6. As can be seen from the figure, the full battery assembled with the composite graphite negative electrode has a capacity retention rate of 95% after 300 cycles at a high rate of 4C, while the full battery assembled with the graphite negative electrode has only an 88% retention rate after 300 cycles. It can be seen that the graphite of the composite lithium-silver alloy has good kinetics at high rates, and therefore exhibits high specific capacity and cycle stability.
[0098] Embodiment 7
[0099] In an inert atmosphere, lithium and carbon nanotubes are melted to prepare a lithium-carbon alloy, and 0.01 g of lithium-carbon alloy (with micron-sized grains) is added to 1 mL of VC / DME / DEC organic solvent (volume ratio 1:1:18) and stirred for 1 hour to obtain a lithium-containing particle slurry containing lithium particles. After adding two functional additives, lithium nitrate (5% by mass) and thiourea (0.1% by mass), to the lithium-containing particle slurry and mixing them evenly, the composite slurry is coated on a copper foil to obtain a composite thin lithium negative electrode with controllable thickness (e.g., 0.1-100 μm) on the copper foil. A full battery was assembled with a composite thin lithium negative electrode (7 μm, Li slurry) and a lithium cobalt oxide positive electrode (the preparation process of the lithium cobalt oxide positive electrode was the same as the preparation of the positive electrode in Example 5), a full battery was assembled with a commercial thin lithium (50 μm, Li) and a lithium cobalt oxide positive electrode, an electrolyte (1.0 M LiPF6 in EC:EMC:DMC=1:1:1, volume ratio) was added, and the electrochemical performance of the full battery was tested (wherein, the use of commercial thin lithium Li to construct a full battery served as a control).
[0100] Fig.12 This is the capacity retention rate diagram of the full battery prepared in Example 7. As can be seen from the figure, the full battery assembled with the composite thin lithium negative electrode has high cycle stability at a high rate of 2C. This result shows that the composite three-dimensional structure thin lithium negative electrode has good electrochemical activity under high current due to its good ion / electronic conductivity, which can effectively inhibit the growth of dendrites and increase the reaction rate under high current. In addition, since the thinner the electrode sheet, the worse the performance, Fig.12 The thickness of the commercial thin lithium used in comparison is 50 μm, while the thickness of the composite thin lithium negative electrode obtained in this embodiment is 7 μm. In such an ultra-thin case, the performance obtained is better than that of the commercial thin lithium, with obvious advantages.
[0101] Embodiment 8
[0102] In an inert atmosphere, lithium and indium are melted to prepare a lithium-indium alloy (with micron-sized grains and an indium mass percentage content of 5%), and 0.01 g of the lithium-indium alloy is added to 1 mL of TO / DMC / DEC organic solvent (volume ratio 1:1:1) and stirred for 10 h to obtain a lithium-containing particle slurry containing the lithium-indium alloy. Lithium lanthanum zirconium oxide solid electrolyte (mass percentage content 5%) and graphene (mass percentage content 5%) are added to the lithium-containing particle slurry and mixed evenly to obtain a composite slurry, and the composite slurry is coated on a copper foil and dried to obtain a three-dimensional composite negative electrode (Li slurry) with a controllable thickness (10 μm in this embodiment) on the copper foil. The three-dimensional composite negative electrode (Li slurry), lithium phosphorus sulfur chlorine solid electrolyte, and nickel cobalt manganese oxide positive electrode are sequentially placed in a mold battery to assemble an all-solid-state battery, and the electrochemical performance of the all-solid-state battery is tested.
[0103] At the same time, commercial thin lithium (50μm, Li), lithium phosphorus sulfur chlorine solid electrolyte, and nickel cobalt manganese oxide positive electrode were put into the mold battery to assemble an all-solid-state battery, and the electrochemical performance of the all-solid-state battery was tested as a control sample.
[0104] Fig.13 This is the capacity retention rate diagram of the all-solid-state battery prepared in Example 8. As can be seen from the figure, the all-solid-state battery assembled with the composite negative electrode has high cycle stability at a rate of 0.5C. This result shows that the three-dimensional composite structure thin lithium alloy negative electrode has good ion / electronic conductivity, good electrochemical activity under high current, and can effectively inhibit the growth of dendrites. In addition, since the thinner the electrode sheet, the worse the performance, Fig.13 The commercial thin lithium used in comparison has a thickness of 50 μm, while the three-dimensional composite negative electrode obtained in this embodiment has a thickness of 10 μm. In such an ultra-thin case, the obtained performance is better than that of the commercial thin lithium, with obvious advantages.
[0105] Embodiment 9
[0106] In an inert atmosphere, silver, tin, magnesium, aluminum, sodium, silicon, zinc, boron, gold, and carbon are each added to 2wt% and melted with lithium metal to prepare high entropy composite lithium, and the structure is controlled to make the high entropy composite lithium have micron-sized grains. 0.01g lithium high entropy lithium is added to 1mL FEC:VC:EC:DOL:DOX:DEC organic solvent (volume ratio 1:1:1:1:1:5) and stirred for 5h to obtain a lithium-containing particle slurry containing high entropy composite lithium. 0.1M lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalate borate), lithium difluoro(oxalate borate), lithium bis(difluorosulfonyl imide), lithium nitrate, lithium fluoride, lithium phosphorus sulfur chloride, lithium lanthanum zirconium oxygen, and lithium iodide are added to the lithium-containing particle slurry and stirred to form a 1M high entropy electrolyte. Further, 1% (mass percentage) of aluminum trifluorosulfonate and azobisisobutyronitrile initiator are added to obtain a uniformly dispersed lithium-containing particle slurry (Li slurry). The silicon negative electrode, high entropy lithium-containing particle slurry, separator and lithium cobalt oxide positive electrode were assembled in sequence into a polymer solid-state full battery, and the electrochemical performance of the polymer solid-state full battery was tested.
[0107] At the same time, the silicon negative electrode, the separator and the lithium cobalt oxide positive electrode were assembled in sequence to form a polymer solid-state full battery (i.e., without introducing the high-entropy lithium-containing particle slurry), and the electrochemical performance of the polymer solid-state full battery was tested as a control sample.
[0108] Fig.14This is a graph of the capacity retention rate of the solid-state battery prepared in Example 9. As can be seen from the figure, the high-entropy in-situ polymer solid-state battery prepared by introducing high-entropy lithium, high-entropy salt and high-entropy solvent has high cycle stability at 1C rate. This result shows that directly adding lithium powder to the polymer solid electrolyte can effectively compensate for the lithium loss of the negative electrode, increase the capacity of the battery, and improve the cycle stability of the battery.
[0109] Embodiment 10
[0110] Under an inert atmosphere, 0.01 g of lithium foil (with micron-sized crystals) was added to 1 mL of EC / DEC organic solvent (volume ratio 1:19) and stirred (speed 800 rpm). After 10 hours, a lithium-containing particle slurry (Li slurry) containing lithium particles was obtained. The lithium-containing particles were detected using an X-ray photoelectron spectroscopy (XPS) instrument.
[0111] like Fig.15 As shown in (a) and (b) in FIG. 1 , the surface of the lithium-containing particles is an interface structure dominated by organic lithium. When the depth of argon ion etching is 10 nm, as shown in FIG. Fig.15 As shown in (c) and (d), the surface of the lithium-containing particles is an organic-inorganic composite structure. Therefore, it can be inferred that the passivator partially decomposes away from the lithium metal surface to form an organic passivation layer (ROCO2Li). The passivator completely decomposes near the lithium metal surface to form an inorganic / organic passivation layer (Li2CO3 / ROCO2Li). The peak of lithium metal appears, which indicates that the thickness of the interface layer is 10nm.
[0112] The synthesized lithium-containing particle slurry is placed in an environment with a humidity of more than 30% and a temperature of about 30°C. Fig.16 As shown, the lithium-containing particle slurry synthesized in Example 10 still maintains metallic luster after being placed in the air for 1 day and 7 days. It can be seen that the lithium-containing particle slurry synthesized in this application has good air stability.
[0113] Embodiment 11
[0114] Under an inert atmosphere, a lithium-tin alloy (with micron-sized grains and a tin mass percentage content of 20%) was rapidly annealed at 300°C (cooling rate 30°C / min). 0.01 g of the annealed lithium-tin alloy was added to 1 mL of EC / DEC / DMC organic solvent (volume ratio 1:8:1) and stirred (speed 2000 rpm). After 10 minutes, a lithium-containing particle slurry (Lislurry) containing spherical lithium particles was obtained.
[0115] Embodiment 12
[0116] Under an inert atmosphere, 0.01 g of lithium foil (with micron-sized grains) was added to 1 mL of EC / DEC / DMC organic solvent (volume ratio 1:1:1) and stirred (speed 100 rpm). After 30 hours, a lithium-containing particle slurry (Lislurry) containing lithium particles was obtained.
[0117] Fig.17 The morphology of lithium particles in the lithium-containing particle slurry synthesized in Example 12. As can be seen from the figure, the lithium particles are in the form of 1 μm-level flakes, the thickness of the flakes is in the order of hundreds of nanometers, and the surface has uniformly distributed nanopores.
[0118] Embodiment 13
[0119] Under an inert atmosphere, 0.01 g of cold-pressed lithium foil (with nanoscale grains) was added to 3 mL of EC / DEC / DMSO organic solvent (volume ratio 1:4:0.1) and stirred (speed 2000 rpm). After 1 hour, a lithium-containing particle slurry (Li slurry) containing lithium particles was obtained.
[0120] Fig.18 The morphology of lithium particles in the lithium-containing particle slurry synthesized in Example 13. As can be seen from the figure, the morphology of the lithium particles is a thin flake of 100 nm level.
[0121] The reagents used in the above embodiments are all commercially available; in addition, the inert atmosphere used in the above embodiments is argon. The slurries containing lithium particles obtained in the above embodiments are all prepared at room temperature (that is, the reaction between the organic solvent and the lithium-containing metal material is carried out at room temperature). In addition, the thickness of the slurry load and the thickness of the assembled self-supporting film can be flexibly controlled.
[0122] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium-containing particle slurry, characterized in that: The method comprises using a mixed organic solvent formed by mixing an etchant and a passivator, dispersing a material containing lithium metal in the mixed organic solvent, etching the grain boundaries in the material containing lithium metal by using the etchant, and passivating the grain surfaces by using the passivator, thereby obtaining a slurry containing stable micron-scale and / or nano-scale lithium-containing particles; wherein the material containing lithium metal has micron-scale and / or nano-scale grains, and the lithium metal is at least one of a single metallic lithium substance and a lithium alloy; The mixed organic solvent is completely composed of a liquid organic solvent, wherein the etchant is selected from at least one of diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), ethanol (EtOH), and dimethyl sulfoxide (DMSO); The passivating agent is selected from at least one of ethylene carbonate (EC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), 1,3-dioxane (DOX), and trioxane (TO); The volume percentage of the passivating agent in the mixed organic solvent is 5%-50%.
2. The method for preparing a lithium-containing particle slurry according to claim 1, characterized in that: The material containing lithium metal is at least one of lithium metal, lithium alloy, lithium metal-based composite material, lithium solid solution, and lithium solid solution-based composite material; The metal lithium-based composite material is a composite material of lithium metal and carbon material, or a composite material of lithium metal and solid electrolyte; The elements contained in the lithium solid solution, in addition to the Li element, also include at least one of the following elements: silver element, magnesium element, gold element, zinc element, aluminum element, and platinum element; The lithium solid solution-based composite material is a composite material of a lithium solid solution and a carbon material, or a composite material of a lithium solid solution and a solid electrolyte; The lithium-containing particles are in the form of at least one of spheres and flakes; The surface of the lithium-containing particle has an interface structure generated by passivation, and the interface structure is at least one of an organic substance or an organic-inorganic composite.
3. The method for preparing a lithium-containing particle slurry according to claim 1, characterized in that: After the lithium metal-containing material is dispersed in the mixed organic solvent, the reaction system is further stirred to accelerate the reaction.
4. The method for preparing a lithium-containing particle slurry according to claim 1, characterized in that: After the reaction, the slurry containing lithium particles is further added with a functional additive; the functional additive is selected from: at least one of ethylenediaminetetraacetic acid, silane coupling agent, thiourea, polyacrylic acid, polyvinylidene fluoride, polyethylene glycol, glycerol, polyethylene oxide, silver nitrate, silver fluoride, and tin fluoride; or selected from: alkyl lithium, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium difluorobis(oxalatophosphate), lithium nitrate, lithium fluoride, lithium nitride, lithium oxide, lithium carbonate, and hydroxide. At least one of lithium, lithium hydride, aryl lithium, amide lithium, lithium phosphorus sulfur, lithium lanthanum zirconium oxide, lithium iodide, naphthalene lithium, anthracene lithium, and biphenyl lithium; or at least one of carbon black, carbon nanotubes, vapor-grown carbon fiber reinforcement, graphene, acetylene black, and Ketjen black; or at least one of nitrogen diisobutyronitrile, azodiisopropylbenzene, dibenzoyl peroxide, dilauroyl peroxide, 1,3,2-dioxazolidinone-2,2-dioxide, tin trifluoromethanesulfonate, and magnesium trifluoromethanesulfonate; the mass percentage of the functional additive in the slurry obtained after adding is 0-50%.
5. A lithium ion battery pre-lithiation electrode, characterized in that: The slurry containing lithium particles prepared by the preparation method according to any one of claims 1 to 4 is loaded on the electrode of a lithium secondary battery, so that pre-lithiation can be completed after injecting an electrolyte.
6. The lithium-ion battery pre-lithiation electrode according to claim 5, characterized in that: The loading is specifically achieved by dripping, coating, spraying, spinning or 3D printing.
7. A lithium metal-based electrode, characterized in that The method comprises loading a slurry of lithium-containing particles obtained by the preparation method according to any one of claims 1 to 4 on a current collector to form a lithium metal-based electrode on the current collector; or assembling a slurry of lithium-containing particles obtained by the preparation method according to any one of claims 1 to 4 together with a supporting material into a self-supporting film to obtain a lithium metal-based electrode.
8. The lithium metal-based electrode according to claim 7, characterized in that The loading is specifically achieved by dripping, coating, spraying, spinning or 3D printing; the supporting material is selected from carbon nanotubes and carbon fibers; The thickness of the lithium metal-based electrode is 0.1-100 μm 。 9. A lithium-based solid electrode, characterized in that: The integrated lithium-based solid electrode is obtained by compounding the slurry containing lithium particles obtained by the preparation method according to any one of claims 1 to 4 with a lithium battery solid electrolyte.
10. Use of the lithium-ion battery pre-lithiation electrode according to claim 5 or 6, the lithium metal-based electrode according to claim 7 or 8, or the lithium-based solid-state electrode according to claim 9 in a lithium secondary battery.
Citation Information
Patent Citations
Flake-like lithium metal powder and preparation method thereof
CN108832116A
Lithium ion battery pole piece and diaphragm compounding method and lithium ion battery
CN113300051A
Stabilized, pure lithium metal powder and method for producing the same
CN103379972A
Lithium element supplementing method for electrode of lithium ion battery
CN103943825A
Preparation method for passivation lithium powder
CN108176859A
Cited By
Sulfide electrolyte, composition and method for preparing sulfide electrolyte, and battery
CN122418013A